2017
DOI: 10.4172/2157-7471.1000413
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Potato Brown Leaf Spot Disease Caused by Alternaria alternata Using Brevibacillus formosus Strain DSM 9885 and Brevibacillus brevis Strain NBRC 15304

Abstract: Brown leaf spot is one of the prevalent diseases caused by Alternaria alternata in different growing areas of potato worldwide. Eight A. alternata isolates were screened from forty-two isolates collected from different potato growing regions in four Egyptian governorates viz, North Sinai (Baloza), Beheira (El-Nubaria and Wadi El-Natrun), Ismailia (Abu Suweir, Fayed and Tell El-Kebir), Sharqia (New Salheya and El-Husseiniya). The virulence of the isolates was tested based on the Per cent of Disease Index (PDI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…Basamma and Shripad Kulkarni (2017) found that foliar application of B. subtilis at 10g/l reduced the early blight incidence in tomato caused A. alternata and increased the plant growth promotion by recording the highest number of branches, fruits and fruit weight per plant. Ahmed (2017) tested the efficacy of two bacterial antagonists, namely Brevibacillus formosus strain DSM 9885 and Brevibacillus brevis strain NBRC 15304, against the brown leaf spot of potato under greenhouse condition. The combined application of these two antagonists was found to be superior in their efficacy against disease than the individual applications.…”
Section: Resultsmentioning
confidence: 99%
“…Basamma and Shripad Kulkarni (2017) found that foliar application of B. subtilis at 10g/l reduced the early blight incidence in tomato caused A. alternata and increased the plant growth promotion by recording the highest number of branches, fruits and fruit weight per plant. Ahmed (2017) tested the efficacy of two bacterial antagonists, namely Brevibacillus formosus strain DSM 9885 and Brevibacillus brevis strain NBRC 15304, against the brown leaf spot of potato under greenhouse condition. The combined application of these two antagonists was found to be superior in their efficacy against disease than the individual applications.…”
Section: Resultsmentioning
confidence: 99%
“…Brevibacillus brevis produced useful peptide antibiotic gramicidin S, which attacks the lipid bilayer of the membranes of organisms [28]. Brevibacillus is playing an important role as bio-remediation factor to combat the contamination resulted by toxic metals and reduce the environmental pollution in agricultural soils, water, and the atmosphere.…”
Section: Biocontrol and Bioremediationmentioning
confidence: 99%
“…effects in suppression of Salvia officinalis wilt and root rot diseases effectiveness probably due to the production of several inhibitory metabolites like HCN, chitinase, and siderophore. Ahmed[28] studied the effect of Brevibacillus formosus strain DSM 9885 and Brevibacillus brevis strain NBRC 15304 as a biological control agent on potato brown leaf spot disease caused by Alternaria alternata, the study demonstrated that the use of the tested Brevibacillus strains could enhance resistance to brown leaf spot in potato. The linear mycelial growth and spore germination of A. alternata was inhibited by both of tested bacterial isolates with reduction of disease symptoms, where the effects were determined in vitro through detached leaves and under greenhouse conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biological control method is a suitable for post harvest applications (Mari and Guizzardi, 1998) due to storage conditions where are controlled many parameters and biological control agents can confront with the pathogens, directly (Wilson and Pusey, 1985). In order to prevent post harvest losses, different researchers were determined fungi, bacteria and yeasts used successfully in in vitro and in vivo assay in biological control of dry and wet rot in fruits (Schisler et al, 1997;Kotan et al, 1999Kotan et al, , 2002Roco and Perez, 2001;Sadfi et al, 2002;Sempere and Santamarina, 2007;Panwar et al, 2013;Pane andZaccardelli, 2015, Ghosh et al, 2016;Ahmed, 2017).…”
Section: Introductionmentioning
confidence: 99%